2011
DOI: 10.3310/hta15400
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and economic evaluation of cilostazol, naftidrofuryl oxalate, pentoxifylline and inositol nicotinate for the treatment of intermittent claudication in people with peripheral arterial disease.

Abstract: An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per issue and for the rest of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 47 publications
0
39
0
3
Order By: Relevance
“…Cilostazol is commonly used in symptomatic IC due to its ability to decrease platelet function and increase vasodilation. Systematic reviews of the efficacy of cilostazol in IC report an increase in maximal walking distance and improvements in quality of life based upon the Short Form 36 health-related qualityof-life questionnaire, and improvement in ankle-brachial pressure index (ABPI) when compared with placebo [29,30]. No benefit in mortality has consistently been found with cilostazol.…”
Section: Intermittent Claudicationmentioning
confidence: 98%
See 1 more Smart Citation
“…Cilostazol is commonly used in symptomatic IC due to its ability to decrease platelet function and increase vasodilation. Systematic reviews of the efficacy of cilostazol in IC report an increase in maximal walking distance and improvements in quality of life based upon the Short Form 36 health-related qualityof-life questionnaire, and improvement in ankle-brachial pressure index (ABPI) when compared with placebo [29,30]. No benefit in mortality has consistently been found with cilostazol.…”
Section: Intermittent Claudicationmentioning
confidence: 98%
“…Significantly lower ABPI (0.81 vs. 0.72, p \ 0.05) was found in the cilostazol group as compared to controls. Others have demonstrated that adding cilostazol to baseline aspirin therapy reduced MACE and improved ABPI in patients with IC who underwent FP endovascular procedures [29].…”
Section: Reducing Restenosis After Endovascular Proceduresmentioning
confidence: 99%
“…However, these agents are either not sufficiently efficacious, or have an insufficient evidence base, to be widely included in clinical recommendations [3,30]. Anti-hypertensive therapy is a mainstay of CVD risk-reduction, and effective treatment of hypertension has been shown to significantly reduce mortality in patients with symptomatic PAD.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Bebe et al wies in seiner Studie mit 2×50 mg und 2×100 mg eine Dosisabhängigkeit nach [5]. Zusätzlich konnte teils eine Verbesserung der Lebensqualität, teilweise jedoch auch nicht nachgewiesen werden [33]. Die Ergebnisse wurden 2008 in der Cochrane-Analyse bestätigt [31].…”
Section: Sicherheitsprofilunclassified
“…B. die A. femoralis superficialis scheinen nach interventionellen Eingriffen durch Entzündungsreaktionen häufig zu restenosieren. Hierzu konnte eine aktuelle japanische Studie von Soga et al anhand von 618 Patienten mit einer kritischen Extremitätenischämie über 5 Jahre nach endovaskulärer Therapie eine erhöhte Offenheitsrate sowie eine verbesserte Rate an Extremitätenerhalt durch die zusätzliche Einnahme von Cilostazol gegenüber der Kontrollgruppe ohne Cilostazol nachweisen [33]. Bemerkenswert in dieser Studie war, dass das Ausbleiben einer chirurgischen Konversion in den 5 Jahren in der Cilostazolgruppe signifikant höher war.…”
Section: Gehtrainingunclassified